CRISIS MANAGEMENT OF ENVIRONMENTAL POLLUTION BY PT PERTAMINA EP ASSET 4 FIELD CEPU (CASE STUDY IN NGELO, CEPU SUBDISTRICT, BLORA REGENCY) - Ken Anne Kartika Suri; Dr. Dra. Sri Budi Lestari, SU (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2016)
The background of this research is crisis condition that caused by the conflict between PT Pertamina EP Asset 4 Field Cepu with the citizens of Ngelo, Cepu Subdistict, Blora Regency, due to environmental pollution which derived from operation activites in MGS (Main Gathering Station) Menggung. The purpose of the research is to describe how the crisis management pattern was done by public relations PT Pertamina EP Asset 4 Field Cepu to resolve the conflict between the company and citizens of Ngelo, Cepu Subdistrict, blora Regency due to pollution. An effort to solve the problems and research purpose was done by using the theory of Cluster Crisis, Hertfordshire Oil Storage Limited (HOSL) Crisis Management Process, Boundary Spanning and Environmental Scanning Theory, Situational of The Public (STP) Theory, and Image Restoration Theory. This research use case study analysis method. Data analysis unit that investigated in this research is PT Pertamina EP Asset 4 Field Cepu and citizens of Ngelo, Cepu Subdistrict, Blora Regency. The result showed that PT Pertamina EP Asset 4 Field Cepu try to manage the crisis through checks in Main Gathering Station Menggung at an early stage of crisis (pra crisis). Communication built by PT Pertamina EP Asset 4 Field Cepu with the society directly, besides the handling in operational way during the crisis is still continuing by close the oil catcher and made anticipation by raising up the hedge of main gathering station menggung. PT Pertamina EP Asset 4 Field Cepu was also doing corporate social responsibility program (CSR) for Ngelo citizens doing the corporate social responsibility program in some sectors like health, infrastructure, environment, education, economic empowerment, and education during the crisis (on going) crisis management. PT Pertamina EP Asset 4 Field Cepu use strategy corrective action and mortification (acknowledge faults) to rebuild image organization damage caused by crisis will be meetings with Ngelo citizens and dialogue by the mass media. PT Pertamina EP Asset Field Cepu suggested to build a team crisis that consists of of people from related function to coordinate crisis management pattern from the problem that faced.